2011
DOI: 10.1016/j.trstmh.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Loss of genetic diversity in Culex quinquefasciatus targeted by a lymphatic filariasis vector control program in Recife, Brazil

Abstract: Recife is one of the largest cities in north-eastern Brazil and is endemic for lymphatic filariasis transmitted by Culex quinquefasciatus. Since 2003 a control program has targeted mosquito larvae by elimination of breeding sites and bimonthly application of Bacillus sphaericus. To assess the impact of this program on the local vector population we monitored the genetic diversity and differentiation of Cx. quinquefasciatus using microsatellites and a B. sphaericus-resistance associated mutation (cqm1(REC)) ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In our study, we found that A R declined within most populations over time, although the decline was significant in only three out of the seven cases. A reduction in allelic richness was also observed in a small-scale study of Culex quinquefasciatus in Recife, Brazil [58]. This mosquito population was controlled through source reduction and the biological control of larvae.…”
Section: Discussionmentioning
confidence: 61%
“…In our study, we found that A R declined within most populations over time, although the decline was significant in only three out of the seven cases. A reduction in allelic richness was also observed in a small-scale study of Culex quinquefasciatus in Recife, Brazil [58]. This mosquito population was controlled through source reduction and the biological control of larvae.…”
Section: Discussionmentioning
confidence: 61%
“…Conversely, some mosquito populations regularly experience reductions in numbers because of vector control efforts, which could influence allele frequencies in these natural populations even though they are in HWE. For example, Cartaxo and others47 found that genetic diversity of populations of Cx. quinquefasciatus in Brazil decreased over a three-year period because of control efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in population size can reduce A R by removing rare alleles, and a campaign against lymphatic filariasis did significantly reduce allelic richness in a Culex quinquefasciatus population in Brazil (Cartaxo et al. ). However, in populations that have fluctuated multiple times over the course of the last hundred generations or so, few rare alleles remain to be lost, and we would not necessarily expect to see rare allele loss reflected in A R during one of these periodical population size reductions.…”
Section: Discussionmentioning
confidence: 99%